(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The effect of replacing different levels of soaked chickpea seeds for groundnut cakes on broiler chicken was evaluated. An experiment was carried out using 200 one-day-old unsexed Ross 308 broiler chicks in a completely random design. Different levels of soaked chickpea seeds replaced groundnut cake at 0, 15, 30, 45 and 60%. Five starter and finisher diets were formulated according to National Research Council (NRC, 1994). Growth performance, blood biochemical parameters, carcass characteristics and histopathological aspects of liver and small intestine were studied. The chicks were randomly divided into the five dietary treatment groups; each of them was subdivided into four replicates of ten birds each. The experiment was conducted in an open- sided poultry house. The chicks were brooded and reared from one-day-old to six weeks of age in (1x1 m) pens with wood shavings litter. The results regarding chemical composition of chickpea seeds indicated positive nutritional components as it includes relatively moderate protein (20.2%) and high metabolizable energy (3290 kcal/kg). Body weight gain and FCR during starter phase were significantly (P≤0.05) deteriorated for birds fed on diet with 60% replacement level versus those fed the other diets. During finisher phase, significant (P≤0.05) improvement of PER was shown by birds fed on 30, 45 and 60% compared to 0 and 15% replacement level. For the overall period, birds fed on 30% replacement level grew insignificantly (P≥0.05) faster by 6.4% when compared to control. Dietary treatments had significant (P≤0.05) inconsistently effect on dressing%. Birds fed on 60% replacement level of soaked chickpea seeds showed significantly (p<0.05) the highest plasma glucose compared to those fed diets A, B and D. Plasma Alanine amino transferase (ALT)/glutamate-pyruvate transaminase (GPT) and alkaline phosphatase (ALP) for birds fed different diets were not significantly (p≥0.05) different compared to the control. It could be concluded that soaked chickpea seeds could replace 30% of inclusion level of groundnut cake in broiler diets with improvement on overall performance. It is suggested that further research is necessary to evaluate other treatments such as roasting and cooking for chickpea seeds.